Subordinate Clauses Used in Anak Boru Sanina in Simalungun Wedding Ceremony - Nurhasanah Purba; Mulyadi (Lakhomi Journal Scientific Journal of Culture, 2020)
The aims of this study is to find out subordinative clause in Anak boru sanina utterances in simakungun wedding ceremony. The method used in this study is a qualitative descriptive method. The result shows that the study is found only adverbial clause while noun clause and relative clause are do not found. The kind of adverbial clause that found are 13 clauses containing of purpose, 9 clauses are containing of manner, 4 clause are containing of causes, 2 clauses are containing of effect, and 2 clauses are containing of condition. The discussion shows that adverbial clause most appear in Anak Boru Sanina utterances in Simalungun wedding ceremony because in this position Anak Boru Sanina as the leader of wedding ceremony so all the utterances containing of adverb clause and the most is purpose to carry out the role of Simalungun culture.